التقعيد الفقهي وأثره في القضايا المعاصرة - عليوات، نضال داود يوسف; ضميرية، عثمان جمعة (جامعة الشارقة, 2018)
تدور مادة هذا البحث حول أثر التقعيد الفقهي في التوصل للأحكام الشرعية للقضايا المعاصرة، وقد تناول بالتحليل معنى التقعيد الفقهي وأهميته، وألمح إلى أن هذا المعنى لا يتحقق ببناء القاعدة الفقهية فحسب، بل لا بد من ظهور أثره بالاستدلال بها، حيث يضمن ذلك استمرار عملية الاجتهاد، وذلك من خلال المبحث الأول، وأبرز المبحث الثاني، أثر القواعد الفقهية في استنباط الأحكام الشرعية للمسائل المستجدة التي تظهر في كل حين، عبر نماذج ساقها لقضايا معاصرة، كان للقواعد الفقهية الكلية الخمسة وبعض ما تفرع عنها، الأثر الأبرز في إيجاد الأحكام الشرعية لها، مما يعني -بما لا يدع مجالا للشك- بقاء الحيوية في التشريع الإسلامي الحنيف، وصلاحيته لكل زمان ومكان.
The substance of this research is about the impact of "Formulating Fiqh Principles" on devising Islamic Provisions regarding contemporary issues. In the first part, we analyzed the meaning of formulating fiqh principles and its importance, and demonstrated that this meaning is not achieved by constructing the jurisprudential rule only, but by reflecting it through reasoning and deduction, which ensures the continuation of the process of Ijtihad. In the second part, we highlighted the impact of jurisprudence rules on formulating Shari’a provisions regarding contemporary issues that arise all the time by studying some examples of these issues. The five jurisprudential rules and some of their ramifications have had the most significant effect on devising Shari’a provisions, which undoubtedly means that Islamic legislation remains vital and valid for all time and place.
Keywords: الفقه الإسلامى -- القواعد الفقهية -- التقعيد الفقهي -- القضايا المعاصرة -- الشريعة الإسلامية